The valid measurement of running economy in runners - Shaw, A. J.; Ingham, S. A.; Folland, J. P. (Medicine & Science in Sports & Exercise, 2014)
Oxygen cost (OC) is commonly used to assess an athlete`s running economy, although the validity of this measure is often overlooked.